Pengaruh Lebar dan Ketebalan Komposit C/CuO Berbasis Karbon Aktif Pelepah Kelapa Sawit Terhadap Karakteristik Material Termoelektrik - Novriansyah, Edo; Putra, Ananda; Azhar, Minda; Nizar, Umar Kalmar (Periodic, 2024)
Abstract -Electrical energy is energy that is really needed by humans, one way to save electrical energy is to use the thermoelectric method. Thermoelectric materials are materials that can convert heat energy into electrical energy through the Seebeck effect. This research aims to determine the effect of the size of the Active Carbon/Cuo composite material with a high Seebeck coefficient and apply it as a thermoelectric generator. In this study, variations in the size of the mold material were carried out with thickness (0.5 0.8 1 1.3 and 1.5) cm, width (1 1.3 1.6 2.5) and length 5 cm. From the research results, it can be seen that materials with sizes of 0.5 cm and 1 cm have the highest thermal conductivity, namely 0.195 mS.cm-1 and 0.0964 mS.cm-1, the lowest thermal conductivity is 0.06J/s and 0.08J/s, and the highest electrical voltage (Seebeck effect), namely 0.02 mV/K and 0.012 mV/K. Furthermore, applying this material to a generator is capable of producing an electrical voltage of 1.7V at a temperature of 80℃.